Geographical traceability of gelatin in China using stable isotope ratio analysis - Li, Shuang; Jiang, Di; Li, Jinglin; Ma, Yuhua; Yao, Jian; Du, Lin; Xu, Yisheng; Qian, Yuan (Frontiers in Nutrition, 2023)
Geographical traceability is crucial to the quality and safety control of gelatin. However, currently, methods for gelatin traceability have not been established around the world. The aim of this study was to investigate the possibility of differentiating the geographical origins of gelatin among different regions in China using stable isotope technology. To achieve this objective, 47 bovine stick bones from three different regions (Inner Mongolia, Shandong, and Guangxi) in China were collected, and gelatin was extracted from these bones using an enzymatic method. The fingerprint characteristic of δ13C, δ15N, and δ2H of gelatin from different regions in China were studied. Moreover, the isotopic changes from bone to gelatin during processing were examined to evaluate the effectiveness of these factors as origin indicators. The results of one-way analysis of variance showed that the δ13C, δ15N, and δ2H of gelatin from different regions have significant differences, and using linear discriminant analysis, the correct differentiation of origin reached 97.9%. Certain stable isotope ratio differences were observed during the processing of the processing of bone to gelatin samples. Nonetheless, the fractionation effect caused by processing was not sufficient to influence the identification of gelatin from different origins, which proves that δ13C, δ15N, and δ2H are effective origin indicators of gelatin. In conclusion, stable isotope ratio analysis combined with chemometric analysis can be used as a reliable tool for gelatin traceability.